The information content of treasury bond options concerning future volatility and price jumps - Thomas Busch; Bent Jesper Christensen; Morten Ørregaard Nielsen (Queen's University, Department of Economics, 2006)
We study the relation between realized and implied volatility in the bond market. Realized volatility is constructed from high-frequency (5-minute) returns on 30 year Treasury bond futures. Implied volatility is backed out from prices of associated bond options. Recent nonparametric statistical techniques are used to separate realized volatility into its continuous sample path and jump components, thus enhancing forecasting performance. We generalize the heterogeneous autoregressive (HAR) model to include implied volatility as an additional regressor, and to the separate forecasting of the realized components. We also introduce a new vector HAR (VecHAR) model for the resulting simultaneous system, controlling for possible endogeneity of implied volatility in the forecasting equations. We show that implied volatility is a biased and inefficient forecast in the bond market. However, implied volatility does contain incremental information about future volatility relative to both components of realized volatility, and even subsumes the information content of daily and weekly return based measures. Perhaps surprisingly, the jump component of realized bond return volatility is, to some extent, predictable, and bond options appear to be calibrated to incorporate information about future jumps in Treasury bond prices, and hence interest rates.
Keywords: C22; C32; G1; 330; bipower variation; bond futures options; HAR; Heterogeneous Autoregressive Model; implied volatility; jumps; realized volatility; VecHAR; volatility forecasting; Rentenmarkt; Termingeschäft; Volatilität; Schock; ARCH-Modell; Zeitreihenanalyse